Response of non-loadbearing concrete masonry units with plastic additives to non-destructive tests - San Antonio, Maria Cristelle A.; Peralta, Mathew Harvey T.; Venus, Mary Jane F. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Most studies on non-destructive tests (NDT) of concrete structures as of date deal with conventional concrete used in construction. In the reduction of density of concrete in general, lightweight materials are often used as additives or supplementary aggregates. By using lightweight plastic as an additive in concrete. the contribution of plastic to solid waste pollution has the possibility to be lessened. In this study, the possible effects of plastic on the response of non-loadbearing concrete masonry units (CMU) to NDT were determined. This objective was attained by obtaining NDT parameters such as ultrasonic pulse velocity, wave attenuation and rebound number, and checking these parameters for a possible correlation with the concrete's compressive strength and with the percentage of plastic added. The NDT parameters were obtained through the Ultrasonic Pulse Velocity (UPV) test and the Schmidt Rebound Hammer test, while the compressive strength was obtained through Unconfined Compression Test (UCT). A general equation correlating all the a forementioned NOT parameters to the compressive strength was determined through statistical analysis. This equation can help evaluate the integrity of structures that have been and will be constructed using CMU with plastic. For future implementation of the production of CMU with plastic additives, an optimum percentage of plastic was also determined. Results showed that for a target strength of 600 psi and target density of 1680 kg/m3 (in accordance with requirements set by standard specifications for non-loadbearing CMU), a plastic percentage of 7% is prescribed for mixing in CMU.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete -- Nondestructive testing; Plastics -- Additives